2017
DOI: 10.1177/0340035217696320
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement, cultural competence and two Australian public libraries and Indigenous communities

Abstract: Two examples of community engagement in Australian public libraries, drawn from the author’s experience, are analysed using Sung and Hepworth’s (2013) community engagement model for public libraries and Overall’s (2009) definition of cultural competence in a library and information science framework. The examples are examined for the community engagement characteristics identified by Sung and Hepworth; each is also considered for cultural competence, using the domains which Overall posits are the sites where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Specialist groups such as the Association for Library Service to Children (ALSC), whose competences strongly focus on diversity and inclusion (ALSC, 2020), contribute to ‘strengthen the social justice fabric of the profession’ (Moreillon, 2015: 212). There are many important lessons in the US experience which have already been discussed in the context of Australia (Blackburn, 2014, 2017, 2020) and adopting cultural humility (Hurley et al, 2019) may strengthen our resolve in taking this difficult path.…”
Section: Nine Repertoiresmentioning
confidence: 91%
See 1 more Smart Citation
“…Specialist groups such as the Association for Library Service to Children (ALSC), whose competences strongly focus on diversity and inclusion (ALSC, 2020), contribute to ‘strengthen the social justice fabric of the profession’ (Moreillon, 2015: 212). There are many important lessons in the US experience which have already been discussed in the context of Australia (Blackburn, 2014, 2017, 2020) and adopting cultural humility (Hurley et al, 2019) may strengthen our resolve in taking this difficult path.…”
Section: Nine Repertoiresmentioning
confidence: 91%
“…There are many important lessons in the US experience which have already been discussed in the context of Australia (Blackburn, 2014(Blackburn, , 2017(Blackburn, , 2020 and adopting cultural humility (Hurley et al, 2019) may strengthen our resolve in taking this difficult path.…”
Section: The Lis Education Repertoire (2012-2018) Emergingmentioning
confidence: 97%
“…It has been demonstrated that explorative studies primarily are concerned with intrinsic values, as introduced and discussed in this paper. This implies that values of public libraries generally are perceived as an overall asset to the community, whether this is understood in instrumental and monetary means (Miller, 2017; Aabø, 2009) or in societal concepts of values (Blackburn, 2017; Stenstrom et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The study specifically focuses on what the implications of potential differences in rural community development are and it found that small rural libraries sustained their economic contribution to the community. Blackburn (2017) discusses two examples of community engagement in Australian public libraries by the use of practitioner research methods and finds that the community is vigour and is willing to engage actively with public libraries. These findings acknowledge the potential for public libraries to act as more than just an economic impact factor but as an institution that can provide both instrumental impact and intrinsic added value to society.…”
Section: Introductionmentioning
confidence: 99%